Rule-following and instructional control in obsessive-compulsive behavior. Issue 2 (3rd July 2017) - Hassoulas, Athanasios; McHugh, Louise; Morris, Hannah; Dickenson, Emily Rose; Reed, Phil
ABSTRACT: Two experiments were designed to investigate differences in rule-governed responding between participants who scored either higher or lower on obsessive-compulsive trait measures. In Experiment 1, participants were required to move a marker through a matrix, whereby schedule-sensitive behavior was reinforced on a fixed-ratio 18 or differential-reinforcement-of-low-rate 6 s schedule, which alternated every 2 min. Both groups were further divided into separate instructional conditions, receiving minimal, partial, or accurate instructions. Results revealed that accurate instructions facilitated greater schedule-sensitivity in the high scoring group. Experiment 2 employed random-ratio (RR) and random-interval (RI) schedules of reinforcement to measure schedule-sensitive responding with only minimal instructions provided to all participants. The results showed that the high scoring group maintained a rigid form of responding throughout the task, suggestive of a form of self-generated rule-following. The low scoring groups in both experiments did not appear to require accurate instructions to make contact with the schedule contingencies. The findings provide insight into the maintenance of obsessive-compulsive behavior (OCB).